2015
DOI: 10.1186/s40199-015-0136-3
|View full text |Cite
|
Sign up to set email alerts
|

Blessings in disguise: a review of phytochemical composition and antimicrobial activity of plants belonging to the genus Eryngium

Abstract: Medicinal and edible plants play a crucial role in the prevention and/or mitigation of different human diseases from ancient times to today. In folk medicine, there are different plants used for infectious disease treatment. During the past two decades, much attention has been paid to plants as novel alternative therapeutic agents for the treatment of infectious diseases due to their bioactive natural compounds such as phenol, flavonoids, tannins, etc. The genus Eryngium (Apiaceae) contains more than 250 flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 96 publications
2
80
0
Order By: Relevance
“…The treatment of bacteria and fungi with the fractions gave better results than with extracts. The antimicrobial activity of extracts has been described for some Eryngium species [21][22][23][24][25][26][27][28]. The results of Meot-Duros studies on E. maritimum antimicrobial activity of leaves extracts showed that apolar fractions are generally more active, as compared to polar fraction.…”
Section: Resultsmentioning
confidence: 70%
“…The treatment of bacteria and fungi with the fractions gave better results than with extracts. The antimicrobial activity of extracts has been described for some Eryngium species [21][22][23][24][25][26][27][28]. The results of Meot-Duros studies on E. maritimum antimicrobial activity of leaves extracts showed that apolar fractions are generally more active, as compared to polar fraction.…”
Section: Resultsmentioning
confidence: 70%
“…The composition of E . thorifolium was found to be rich in α ‐pinene, a known antibacterial terpenic compound, which was present in fewer amounts in the other two species …”
Section: Resultsmentioning
confidence: 99%
“…The essential oil was active against all the tested dermatophyte species with MIC values of 0.16 – 0.32 μl/ml and Candida guillermondii with a MIC and MLC of 2.5 μl/ml. Authors suggested that caryophyllene derived compounds (isocaryophyllen‐14‐al (16.2%), 14‐hydroxy‐ β ‐caryophyllene (13.4%), caryophyllene oxide (7.6%) and E ‐ β ‐caryophyllene (6.3%)) are probably the responsible for the antifungal activity …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations